2006
DOI: 10.1038/sj.bmt.1705252
|View full text |Cite
|
Sign up to set email alerts
|

Population pharmacokinetics of intravenous busulfan in patients undergoing hematopoietic stem cell transplantation

Abstract: A population pharmacokinetic analysis was performed in 30 patients who received an intravenous busulfan and cyclophosphamide regimen before hematopoietic stem cell transplantation. Each patient received 0.8 mg/kg as a 2 h infusion every 6 h for 16 doses. A total of 690 concentration measurements were analyzed using the nonlinear mixed effect model (NONMEM) program. A onecompartment model with an additive error model as an intraindividual variability including an interoccasion variability (IOV) in clearance (CL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
32
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 24 publications
(31 reference statements)
11
32
0
1
Order By: Relevance
“…BU has partly solved problems associated with oral administration like the variability in gastric absorption and variations in time to maximum drug concentrations. 27,28 Still, some variability in AUC between patients is observed even with the i.v. formula, and the i.v.…”
Section: Discussionmentioning
confidence: 99%
“…BU has partly solved problems associated with oral administration like the variability in gastric absorption and variations in time to maximum drug concentrations. 27,28 Still, some variability in AUC between patients is observed even with the i.v. formula, and the i.v.…”
Section: Discussionmentioning
confidence: 99%
“…BU pharmacokinetics. 22 However, the value of therapeutic drug monitoring remains crucial. Our study demonstrated no essential difference in PK analysis from earlier published Western data, 19 and this supports the notion that racial factors may not seriously influence the bioactivity of i.v.…”
Section: Discussionmentioning
confidence: 99%
“…BU pharmacokinetics show high inter-and intrapatient consistency. 22 This study with the same population further focused on complete pharmacokinetic profiles with additional clinical and safety data.…”
Section: Introductionmentioning
confidence: 99%
“…7,[26][27][28] Dose targeting based on therapeutic drug monitoring (TDM) also seems to improve event-free survival and survival rates and in some studies VOD-free survival compared with conventional BU treatment. 18,29,30 Despite these improvements, inter-patient variability still exists and the percentage of patients reaching the target AUC after the first dose remains low.…”
Section: Discussionmentioning
confidence: 99%